Validation of Internet Gratification Scale on Indian Undergraduates using Network Psychometrics - Magray, Ajaz Ahmad; Chakraborty, Dr Rajib (South Eastern European Journal of Public Health, 2024)
The Internet Gratification Scale, developed by Dhir et al. (2016), measuresthe Internet Gratifications among adolescents and is based on six factors of Internet gratifications including Information seeking, Exposure, Connection, Coordination, Entertainment and Social influence. In the present study, the scale was validated using the network psychometrics approach for college students in Indian context. The sample subjects were drawn from degree colleges of Jammu and Kashmir Union Territory of India. A total of 662 students were taken from the colleges including both boys (240) and girls (422). We appliedExploratory graph analysis (EGA) by employing the EGAnetpackage in R/R-Studio, which resulted in the yielding of the five clusters of the scale, wherein the node numbers 17, 18 and 19 getting merged with first cluster.These three items pertained to the ‘Exposure’cluster/dimension in the original scale and got merged with ‘Information Seeking’ cluster/dimension. These three items showing split loading were dropped from the scale and the EGA was run again. The network analysis plot obtained after the second run showed a clear 5-cluster/factor structure including Information Seeking, Connection, Entertainment, Social Influence and Coordination. Thereafter ordinal Confirmatory Factor analysis was done. we used the estimator WLSMV for ordinal level data using lavaan package. The analysis revealed the values ofCFI, TLI, RMSEA robust and SRMR bentler as 0.982, 0.980, 0.086 and 0.064respectively which are within the acceptable limits thereby indicate a good fit.Furthermore,edge weight accuracy was calculated through the non-parametric bootstrap confidence interval. The correlation stability coefficient and bootstrapped difference tests were also performed. The plots were generated using the package qgraph.Finally, the structural consistency of the clusters was estimated and found to be within the acceptable limits. The educational and psychometric implications of the study are discussed.